INDEPENDENCE AND IMPARTIALITY OF ARBITRATORS IN INVESTMENT-STATE ARBITRATION: THE BLUE BANK CASE (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2023)
Investment-State arbitration has emerged as an essential mechanism for the resolution of disputes between investors and states. It serves as a means to settle conflicts that may arise from investment agreements or treaties. Central to the integrity and fairness of this arbitration process is the principle of independence and impartiality of arbitrators. The credibility and legitimacy of investment arbitration heavily rely on the assurance that arbitrators possess these qualities, ensuring a level playing field for all parties involved.This paper will analyze the application of the standard for independence and impartiality through the landmark decision of the International Centre for Settlement of Investment Disputes (ICSID) – the Blue Bank Case.The paper delves into the factual background of the dispute, analyzing the arguments presented by both parties in support of their respective proposals for disqualification. It explores the legal framework governing challenges to arbitrators’ independence and impartiality, including relevant provisions of the ICSID Convention and the applicable arbitration rules.Furthermore, the paper critically evaluates the tribunal’s decision on the disqualification proposal, examining the reasoning and legal principles relied upon by the tribunal in reaching its conclusion. The impact of this decision on the broader field of investment arbitration is analyzed, highlighting the significance of maintaining a fair and unbiased tribunal composition in ensuring the legitimacy and integrity of the arbitration process. Finally, it sheds light on the challenges associated with ensuring a fair and unbiased arbitration process in investment disputes and highlights the significance of upholding the principles of independence and impartiality in international arbitration.
Keywords: arbitrator, independence, impartiality, investment-state arbitration, legal standard